Effects of blood hematocrit on cerebral aneurysm flow dynamics and rupture risk assessment: a computational study based on modified Carreau-Yasuda model - G. Harikrishnan; V.M. Akhil; R. Vikas; Charbel Tawk (Results in Engineering, 2025)
Intra-aneurysmal flow dynamics significantly influence the pathophysiology of aneurysm growth and rupture. Blood viscosity is a key determinant of intra-aneurysmal flow dynamics, influenced by factors such as hematocrit, plasma protein, and fibrinogen, among others. This work investigates the impacts of hematocrit on cerebral aneurysm flow dynamics using computational fluid dynamics (CFD). A hematocrit-based non-Newtonian model is proposed and employed to capture the non-Newtonian blood rheology. Based on this model, intra-aneurysmal flow is studied in realistic aneurysm models across a range of hematocrit levels (35, 40, 45, 50, 55, and 60). Key hemodynamic parameters, including time-averaged wall shear stress (TAWSS) and oscillatory shear index (OSI), were evaluated using statistical analysis of variance (ANOVA) to investigate the influence of hematocrit on aneurysm flow dynamics. The findings indicate that elevated hematocrit levels intensify concentrated flow impingement, leading to increased TAWSS and a higher rupture risk at the impingement site. In contrast, lower hematocrit levels result in more diffused flow patterns, reducing rupture risk in these regions. However, low hematocrit is also associated with increased OSI and reduced TAWSS along the aneurysm side walls, potentially elevating rupture risk in those areas.